(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Cardiac tamponade as a manifestation in newly diagnosed hypothyroidism is a rare condition because fluid accumulate slowly. We present a 38-year-old woman with massive pericardial effusion with cardiac tamponade findings in echocardiography without hemodynamic disturbance. Pericardiocentesis was done, but pericardial effusion was not improved. Other secondary causes of pericardial effusion including inflammation, infection, autoimmune disease, and malignancy were ruled out. The patient had a history of thyroidectomy 4 years prior and thyroid function test confirm the diagnosis of hypothyroidism. The patient was given levothyroxine with initial dose of 400 mcg and continued with 100 mcg daily. The pericardial effusion significantly improved in a week.